“Diretor, libera a chave do laboratório de informática!” O gestor escolar como promotor da cultura digital na escola pública - Silva, Eliane Soares da (Universidade do Vale do Rio dos Sinos, 2019)
Technological advancement has triggered the emergence of a new culture, the digital culture, which has been changing thoughts and intervening in people's lifestyles. The school as a space for knowledge construction and training of people can not be oblivious to the insertion of new digital technologies in their pedagogical practice, there is a need for the emergence of a new school with different methodologies and focused on the citizen who lives the culture. day to day, demanding multiple skills from it. The manager is also challenged to change to meet the demand that arises from technological advancement and decentralization of services at school. This study starts from questions regarding the role of the manager facing the new technologies present in the school context. It seeks to argue and understand the importance of the role of the manager for the development of digital culture in the school from the participation of managers in the School Management and Technologies Course, designed and promoted by the Educational Technology Center - NTE of the 27th Regional Education Coordination. from RS. As this research included an empirical study based on the experiences lived in the professional context of this researcher, the methodology was outlined as a case study and a qualitative approach, in an explanatory descriptive research. The data source involved three managers and part of the Pedagogical Political Project - PPP of three state public schools, using observation, interview and document analysis as research instruments. In this sense, the question for this research comes from doubts regarding the school management actions (micro) contextualized in the educational technology policies (macro). In order to know how the managers of state public schools of the 27th Regional Coordination of Education / RS are promoting the development of digital culture in school, after participating in the School Management and Technologies Course promoted by NTE / RS, we seek to analyze how does the manager articulate the activities in the administrative and pedagogical spheres mediated by digital technologies, identify and analyze how the School PPP contemplates the digital culture and analyze the actions that show that the school manager is contributing to the educational technology policies put into practice in schools. The results of this research involved reflection on the need to update the contents proposed in the School Management and Technologies Course with regard to strategic planning and teaching methodologies. Regarding the presence of digital culture in the public school, it was identified that managers initiated this proposal from their participation in the Management Course motivating teachers and managers to participate in Courses offered by the NTE involving digital technological resources present in schools. And by joining the Connected Education Program, managers have installed quality internet in schools. Finally, it was evident in the research, based on the data analyzed, that there is a need for more investments in continuing education of managers and teachers so that educational technology policies achieve their purposes and that the digital culture experienced in today's society is part of school culture. And as an intervention proposal is intended to qualify the School Management and Technologies Course, both in the theoretical dimension with regard to democratic management in school and the skills required for the school manager in contemporary society.
Keywords: Cultura Digital; Gestão Escolar; Tecnologias Digitais; Políticas Educacionais; Digital Culture; School management; Digital Technologies; Educational policies; ACCNPQ::Ciências Humanas::Educação